Where are you from? : Middle-class migrants in the modern world - Raj, Dhooleka Sarhadi, 1969- (University of California Press, 2003)
An exploration of ethnic minority cultural change, this text examines first- and second-generation middle-class South Asian families living in London. It argues that the nostalgia for culture obscures the complexities of change in migrant minority lives.